Acceptance of the COVID-19 vaccine booster dose and associated factors among the elderly in China based on the health belief model (HBM): A national cross-sectional study - Qin, Chenyuan; Yan, Wenxin; Du, Min; Liu, Qiao; Tao, Liyuan; Liu, Min; Liu, Jue (Frontiers in Public Health, 2022)
Background The reluctance of individuals to obtain solid vaccine-induced immunity represents a fundamental challenge to containing the spread of SARS-CoV-2, including its highly mutated variants. We aimed to assess vaccination acceptance and associated factors for the COVID-19 vaccine booster dose among elderly people (≥60 years old) in China, providing a theoretical and practical reference for universal vaccination policy. Methods A national anonymous survey was conducted in mainland China from May 25 to June 8, 2022, using a stratified random sampling method. Individuals 60 years of age and above were the target population. A chi-squared test and Cochran-Armitage test for trend were used to compare and examine vaccine acceptance rates by characteristics. Via a backward stepwise method, multivariable logistic regression models were established to assess factors associated with booster dose acceptance. Two-sided P < 0.05 was considered statistically significant. Results Of 3,321 eligible participants, 82.8% (95% CI: 81.5–84.1%) were willing to receive COVID-19 vaccine booster shots. Concerns about contraindications (38.3%), vaccine safety (32.0%), and limited movement (28.0%) were the main reasons for vaccine hesitancy. Nearly one-third still believed that the booster dose was unnecessary after receiving the initial vaccination. Older adults with a low level of perceived barriers (aOR = 1.86, 95% CI, 1.03–3.38), a high level of perceived benefit (aOR = 2.31, 95% CI, 1.38–3.87), and higher cues to action (moderate, aOR = 2.22, 95% CI, 1.39–3.56; high, aOR = 5.46, 95% CI: 3.44–8.67) were more likely to accept the booster dose. Other major factors affecting the booster dose acceptance rate were occupation, time spent on social media, vaccination history, and a high knowledge score for COVID-19 and vaccines. In addition, for those over 70 years of age, rising awareness of susceptibility could be a better gateway for improving their willingness to get vaccinated. Conclusions A total of 82.8% of recruited older adults were willing to receive the booster dose. Acceptance behaviors were closely related to occupation, time spent on social media, vaccination history, knowledge factors, perception of barriers, and benefit, as well as action cues. Targeted public health measures are a priority for improving the vaccination coverage of valid immunity among the elderly population, not only to prevent infection and poor prognosis caused by emerging variants but also to reduce the huge disease and economic burden caused by the long-term sequelae after SARS-CoV-2 infection.